Distance-construal relationship: Mediating role of perceived control and moderating role of locus of control - Huang, Hui-dan; Zhang, Qi (Frontiers in Psychology, 2023)
The construal level theory (CLT) has been supported and applied widely in social psychology. Yet, what remains unclear is the mechanism behind it. The authors extend the current literature by hypothesizing that perceived control mediates and locus of control (LOC) moderates the effect of psychological distance on the construal level. Four experimental studies were conducted. The results indicate that individuals perceive low (vs. high) situational control from a psychological distance (vs. proximity), and the resultant control perception influences their motivation in control pursuit, producing a high (vs. low) construal level. Moreover, LOC (i.e., one’s chronic control belief) affects an individual’s motivation to pursue control and yields a reversal of distance-construal relationship under external (vs. internal) LOC as a result. Overall, this research first identifies perceived control as a closer predictor of construal level, and the findings are expected to help with influencing human behavior by facilitating individuals’ construal level via control-related constructs.